2017
DOI: 10.3168/jds.2016-11459
|View full text |Cite
|
Sign up to set email alerts
|

Association of anatomical characteristics of teats with quarter-level somatic cell count

Abstract: Mastitis occurs after bacteria successfully traverse the teat orifice and cause an intramammary infection. Anatomical characteristics of the teat are potential risk factors for infection. The objective of this study was to identify potential associations between anatomical characteristics of teats and quarter-level somatic cell count (QSCC) from cows on larger dairy farms in Wisconsin. Teat dimensions (length and diameter at the teat barrel and apex) were measured, and hyperkeratosis scores were assessed for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(59 reference statements)
6
14
0
Order By: Relevance
“…The mean (SE) teat length [42.6 (0.53) mm], teat barrel diameter [21.4 (0.19) mm], and width of teat apex [19.2 (0.13) mm] measured in the current study (Table 1) are similar to data of primiparous cows previously obtained by our research team (Guarin et al, 2017) in a larger cross-sectional study. In that study (Guarin et al, 2017), teats of primiparous cows (n = 618) had mean (SE) length of 42.8 (0.30) mm, barrel diameter of 22.7 (0.10) mm, and teat apex diameter of 19.3 (0.8) mm. As compared with the previous cross-sectional study (Guarin et al, 2017), similar dimensions of front and rear teats were also separately observed, although the diameter of both front and rear teat barrels of cows enrolled in the previous cross sectional study appeared to be about 1 to 1.5 mm wider.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The mean (SE) teat length [42.6 (0.53) mm], teat barrel diameter [21.4 (0.19) mm], and width of teat apex [19.2 (0.13) mm] measured in the current study (Table 1) are similar to data of primiparous cows previously obtained by our research team (Guarin et al, 2017) in a larger cross-sectional study. In that study (Guarin et al, 2017), teats of primiparous cows (n = 618) had mean (SE) length of 42.8 (0.30) mm, barrel diameter of 22.7 (0.10) mm, and teat apex diameter of 19.3 (0.8) mm. As compared with the previous cross-sectional study (Guarin et al, 2017), similar dimensions of front and rear teats were also separately observed, although the diameter of both front and rear teat barrels of cows enrolled in the previous cross sectional study appeared to be about 1 to 1.5 mm wider.…”
Section: Resultssupporting
confidence: 85%
“…These results agree with previous results for teat length but differ from our previous results for teat barrel diameter (Guarín and Ruegg, 2016). The mean (SE) teat length [42.6 (0.53) mm], teat barrel diameter [21.4 (0.19) mm], and width of teat apex [19.2 (0.13) mm] measured in the current study (Table 1) are similar to data of primiparous cows previously obtained by our research team (Guarin et al, 2017) in a larger cross-sectional study. In that study (Guarin et al, 2017), teats of primiparous cows (n = 618) had mean (SE) length of 42.8 (0.30) mm, barrel diameter of 22.7 (0.10) mm, and teat apex diameter of 19.3 (0.8) mm.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations